A multiplicação nos livros do professor usados nos anos iniciais do ensino fundamental em uma cidade de Minas Gerais - Diniz, Michele Jesus (2015)
The dissertation presents an analysis of teacher s textbooks, adopted in public schools in a city in Minas Gerais, focusing on the elaboration of the concept of multiplication from the 1st to 5th year of elementary school. The qualitative analysis about 16 multiplication activities, the most part divided in about four tasks, was developed by the match between the National Curriculum Parameters - PCNs, adopted as guidelines by the investigated textbooks and the Theory of Raymond Duval. As a result, we obtained that most of the initial activities involves conversion. Among the other tasks of the activity involves at least one treatment. We also found an activity involving only treatment, and only three activities without tasks involving treatment. Still, we had a proposal in the guidelines to the teacher, promoting conversion in both directions for proper coordination of semiotic representation registers. Most used registers are mixed, involving the numerical record with natural language